Competitive Strategy Analysis on Ivanova Printography by Foto 2000 Semarang - Yossy Santoso (Journal of Management and Business Environment (JMBE), 2020)
This study aims to identify competitive strategies of Ivanova Printography using SWOT analysis and IE matrix. The data were gathered from the owner, competitors, consumers, and employees. Descriptive qualitative was to interpret the results of the SWOT analysis. The results show that the most important thing is that Ivanova Printography should focus on its strengths, minimize the existing weaknesses and threats, and fill the opportunities available. The best combination is to apply the SO strategy (a combination of Strength and Opportunity). It includes conducting market development (Market Development Strategy) by opening a branch in the area of Semarang, adding new customers by developing markets outside Semarang, adding marketing staff and customer service to deal with customer orders in Semarang that have been increasing and routine, increasing promotions of photo products to increase revenue by conducting more intense promotions through social media such as Twitter, Instagram, BBM, and Whatsapp. The theme of advertisements should be more elegant and focuses on target customers or market segments. The IE matrix results in quadrant I, Grow and Build. The suitable strategies are intensive or integration. The intensive and integration strategy fit for photography industry is to apply market development strategy by expanding market share outside Semarang so that more people recognize Ivanova Printography.